The hellion's waltz - Waite, Olivia (Waite, Olivia. Feminine pursuits, 2021)
"Sophie Roseingrave hates nothing more than a swindler. After her family lost their piano shop to a con man in London, they're trying to start fresh in a new town. Her father is convinced Carrisford is an upright and honest place, but Sophie is not so sure. She has grave suspicions about silk-weaver Madeline Crewe, whose stunning beauty doesn't hide the fact that she's up to something. All Maddie Crewe needs is one big score, one grand heist to properly fund the weavers' union forever. She has found her mark in Mr. Giles, a greedy draper, and the entire association of weavers and tailors and clothing merchants has agreed to help her. The very last thing she needs is a small but determined piano-teacher and composer sticking her nose in other people's business. If Sophie won't be put off, the only thing to do is to seduce her to the cause. Will Sophie's scruples force her to confess the plot before Maddie gets her money? Or will Maddie lose her nerve along with her heart?"--Page 4 of cover.